2009
DOI: 10.1080/15257770903091953
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Glycosylation of Pyrrolo[2,3-d] Pyrimidines with 1-O-Acetyl-2,3,5-Tri-O-Benzoyl-β-D-Ribofuranose: The Formation of Regioisomers During Toyocamycin and 7-Deazainosine Syntheses

Abstract: Glycosylation of silylated 4-amino-6-bromo-5-cyano-7H-pyrrolo[2,3-d]pyrimidine (9) with 1-O-acetyl-2,3,5-tri-O-benzoyl-beta-D-ribofuranose (10) under "one-pot" glycosylation conditions (MeCN, TMSOTf) yielded the N-7 isomer 11 together with the N-1 compound 13 (ratio = 2:1). When the same conditions were applied to 4-hydroxy-7H-pyrrolo[2,3-d]pyrimidine (21) the N-3 isomer 22 was the only glycosylation product formed in almost quantitative yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…Specifically, total synthesis of toyocamycin ( 1 ) by Vorbrüggen glycosylation of ribose 5 and nucleobase 6 was firstly reported by Bobek [20], and further improved by Townsend [21], but during our many repeats of this approach [22,23,24,25], it was found that the N -9 glycosylation product 7 and N -3 glycosylation product 8 were inevitably formed simultaneously (Figure 2). This phenomenon was also reported by several other groups [26,27,28]. The selectivity and equilibrium between N -9 glycosylation product 7 and N -3 glycosylation product 8 were subsequently studied in detail [27].…”
Section: Introductionsupporting
confidence: 70%
“…Specifically, total synthesis of toyocamycin ( 1 ) by Vorbrüggen glycosylation of ribose 5 and nucleobase 6 was firstly reported by Bobek [20], and further improved by Townsend [21], but during our many repeats of this approach [22,23,24,25], it was found that the N -9 glycosylation product 7 and N -3 glycosylation product 8 were inevitably formed simultaneously (Figure 2). This phenomenon was also reported by several other groups [26,27,28]. The selectivity and equilibrium between N -9 glycosylation product 7 and N -3 glycosylation product 8 were subsequently studied in detail [27].…”
Section: Introductionsupporting
confidence: 70%
“…4‐Amino‐5‐cyano‐7H‐pyrrolo[2,3‐d]pyrimidine (4): 4‐Amino‐5‐cyano‐7 H ‐pyrrolo[2,3‐ d ]pyrimidine was prepared analogous to a literature procedure 16. 4‐Amino‐6‐bromo‐5‐cyano‐7 H ‐pyrrolo[2,3‐ d ]pyrimidine (1.60 g, 6.72 mmol) was dissolved in 300 mL ethanol and 300 mL 33% aqueous ammonium hydroxide solution.…”
Section: Methodsmentioning
confidence: 99%
“…Compound (I) was synthesized as described by Leonard et al (2009) and crystallized from aqueous methanol. The crystals decompose above 463 K. For the diffraction experiment, a single crystal was mounted on a MiTeGen MicroMesh fiber in a thin smear of oil.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the crystal structure of toyocamycin was reported by Prusiner & Sundaralingam (1978). Recently, the N-3 regioisomer of toyocamycin was synthesized (Leonard et al, 2009). Generally, purine N-3 nucleosides are relatively labile molecules.…”
Section: Commentmentioning
confidence: 99%